Mitochondrial population structure and post‐glacial dispersal of longnose sucker Catostomus catostomus in Labrador, Canada: evidence for multiple refugial origins and limited ongoing gene flow. Issue 2 (28th June 2016) - Langille, B. L.; Perry, R.; Keefe, D.; Barker, O.; Marshall, H. D.
Abstract : Two hundred and eighty‐seven longnose sucker Catostomus catostomus were collected from 14 lakes in Labrador, 52 from three lakes in Ontario, 43 from two lakes in British Columbia and 32 from a lake in Yukon; a total of 414 in all. The resulting 34 haplotypes (20 in Labrador) contained moderate haplotypic diversity ( h = 0·657) and relatively low nucleotide diversity ( π = 3·730 × 10 −3 . Mean ϕ ST (0·453, P < 0·05) over all populations revealed distinct genetic structuring among C. catostomus populations across Canada, based on province, which was validated by the analysis and spatial analysis of molecular variance ( c. 80% variation between provinces). These results probably reflect the historical imprint of recolonization from different refugia and possibly indicate limited ongoing gene flow within provinces. A haplotype network revealed one major and two minor clades within Labrador that were assigned to the Atlantic, Beringian and Mississippian refugia, respectively, with tests of neutrality and mismatch distribution indicative of a recent population expansion in Labrador, dated between c. 3500 and 8300 years ago.